Le Pilote de Terre-Neuve - France. Dépôt des cartes et plans de la marine ([Paris], 1784)
French pilot guide to Newfoundland containing seven individual coastal maps based on the work of Englishmen James Cook and Michael Lane, with five additional maps of the island and of Saint Pierre and Miquelon. All maps are in similar style. "Sous le Ministère de M. le Maréchal de Castries, Comte d'Alais, Premier Baron né des Etats Languedoc ." (t.p.). -- "Précédé de deux cartes . dressées sur les mêmes Plans . de MM. le M.is de Chabert . J. Cook . le M.is de Verdun, le Ch.er de Borda et Pingré" (t.p.).